Implementation of Transdisciplinary Approaches in Islamic Education to Face Contemporary Global Challenges - Hanif, Abdullah; Wahyudin, Wawan; Sholahuddin, Sholahuddin (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2025)
This research aims to explore the application of a transdisciplinary approach in Islamic education, with a focus on its integration with contemporary global challenges, such as social, environmental, and technological issues. This study uses a qualitative method with a literature study approach. Data is collected from a variety of secondary sources, such as books, journal articles, and official documents. Data analysis was carried out thematically to find patterns and relationships between transdisciplinary approaches and Islamic education. The focus of the research is the theoretical exploration of transdisciplinary education in the Islamic context. The findings show that the transdisciplinary approach at Sakinah Circle successfully integrates various disciplines such as science, mathematics, history, and language with Qur'anic values. Each theme taught, such as